A privacy-preserving Internet of Things device management scheme based on blockchain - Qingsu He; Yu Xu; Zhoubin Liu; Jinhong He; You Sun; Rui Zhang (International Journal of Distributed Sensor Networks)
Blockchain as a new technique has attracted attentions from industry and academics for sharing data across organizations. Many blockchain-based data sharing applications, such as Internet of Things devices management, need privacy-preserving access services over encrypted data with dual capabilities. On one hand, they need to keep the sensitive data private such that others cannot trace and infer sensitive data stored in the block. On the other hand, they need to support fine-grained access control both from time and users’ attributes. However, to the best of our knowledge, no blockchain systems can support time-bound and attributes-based access with high efficiency. In this article, we propose a privacy-preserving Internet of Things devices management scheme based on blockchain, which provides efficient time-bound and attribute-based access and supports key automatic revocation. The analysis and experiments show that our scheme is quite efficient and deployable.